1990
DOI: 10.3168/jds.s0022-0302(90)78979-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Moisture Content of Mixed Rations on Feed Intake and Milk Production of Dairy Cows

Abstract: Rations with target DM proportions of 35, 45,and 65%, attained by soaking the grain mix in water for 24 h, were fed to 46 mid to late lactation, multiparturient dairy cows in two experiments (Experiment 1, 35 and 45% DM; Experiment 2, 45 and 60% DM) to examine the effect of DM percentage of the totally mixed ration on intake and production of cows. Water-soaked concentrate and alfalfa silage were mixed daily and fed ad libitum. Dry matter intake and milk yield and composition were not influenced by the moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
1
9
1
1
Order By: Relevance
“…Despite a 1.4-kg numerical decrease in DMI, the addition of water to the basal TMR had no significant effect on DMI (Table 3); other researchers have also shown no effect of water addition on DMI (Robinson et al, 1990;Leonardi et al, 2005). This, however, was contrary to our hypothesis because it contrasts our previous findings, whereby we found linear decreases in DMI with the addition of water to a TMR containing all wet forages (Miller-Cushon and DeVries, 2009;Felton and DeVries, 2010).…”
contrasting
confidence: 99%
“…Despite a 1.4-kg numerical decrease in DMI, the addition of water to the basal TMR had no significant effect on DMI (Table 3); other researchers have also shown no effect of water addition on DMI (Robinson et al, 1990;Leonardi et al, 2005). This, however, was contrary to our hypothesis because it contrasts our previous findings, whereby we found linear decreases in DMI with the addition of water to a TMR containing all wet forages (Miller-Cushon and DeVries, 2009;Felton and DeVries, 2010).…”
contrasting
confidence: 99%
“…kale, rape) forages reduced DMI via the gut fill effect of intracellular water. Forage intake may be restricted by the time required for cell rupture and the release of water for passage from the rumen (Robinson et al, 1990). Verite and Journet (1970) reported that when water content of fresh perennial ryegrass and forage legumes was greater than 75-85%, forage DM intake decreased in cattle.…”
Section: Discussionmentioning
confidence: 98%
“…In these two trials, the grass was immersed completely in tanks filled with water and then drained for 5 min before being offered to the cows. On the contrary, the addition of water onto conserved forage does not modify the DM intake [29].…”
Section: External Water and Intakementioning
confidence: 93%